The role of foreign direct investment in raising national competitiveness - Rovčanin, Adnan (Naše gospodarstvo, 2008)
In our paper we analyse the appropriate role of FDI policy in raising national competitiveness. The first section discusses the role of FDI in technology transfer, learning and competitiveness. Here we analyse the benefits and costs of internalised technology transfer through FDI flows. In general, this mode of technology transfer is a very efficient means of transferring a package of capital, skills, information, networks, and brand names to developing countries. For many technologies, internalised transfers are the only possible mode of transfer. Also, internalisation may be the most efficient way of transferring the tacit knowledge involved and in the case of rapid technology changes.
Keywords: mednarodni trg kapitala; tuje investicije; direktne investicije; konkurenčnost; Bosna in Hercegovina; Bosnia and Herzegovina